Fatty acid composition and insect resistance in Vigna unguiculata seeds - Piergiovanni, A.R.; Della Gatta, C.D.; Ng, N.Q.; Singh, B.B.; Singh, S.R.; Perrino, P. (Wiley, 1990)
Fatty acid composition of extracted oils from 58 lines of cowpea (Vigna unguicuiata (L) Walp) was investigated by gas‐liquid chromatography (GLC). Considerable variability was observed in the fatty acid profile, though palmitic (16:0), linoleic (18:2) and linolenic (18:3) acids were the dominant components in each line. Correlation analysis shows that seed oil composition differs according to response to Callosobruchus maculatus (F). In fact, besides a group of correlations common to all lines, others were typical of susceptible or resistant lines. In addition the content of linoleic and total unsaturated C18 fatty acids as well as some fatty acid ratios were found to be significantly different between the two groups. This finding suggests that fatty acid analysis can be employed as an easy, fast and cheap procedure for predicting the resistance of cowpea lines to bruchids.